Where the new world is : literature about the U.S. South at global scales - Bone, Martyn, 1974- (New southern studies., 2018)
"Where the New World Is assesses how fiction published since 1980 has resituated the U.S. South globally and how earlier twentieth-century writing already had done so in ways traditional southern literary studies tended to ignore. Martyn Bone argues that this body of fiction has, over the course of some eighty years, challenged received readings and understandings of the U.S. South as a fixed place largely untouched by immigration (or even internal migration) and economic globalization. The writers discussed by Bone emphasize how migration and labor have reconfigured the region's relation to the nation and a range of transnational scales: hemispheric (Jamaica, the Bahamas, Haiti), transatlantic/Black Atlantic (Denmark, England, Mauritania), and transpacific/global southern (Australia, China, Vietnam). Writers under consideration include Zora Neale Hurston, Nella Larsen, John Oliver Killens, Russell Banks, Erna Brodber, Cynthia Shearer, Ha Jin, Monique Truong, Lan Cao, Toni Morrison, Peter Matthiessen, Dave Eggers, and Laila Lalami. The book also seeks to resituate southern studies by drawing on theories of "scale" that originated in human geography. In this way, Bone also offers a new paradigm in which the U.S. South is thoroughly engaged with a range of other scales from the local to the global, making both literature about the region and southern studies itself truly transnational in scope"--